Diplomatic law commentary on the Vienna Convention on diplomatic relations - Denza, Eileen (Oxford commentaries on international law, 2018)
Diplomatic Law was first published in 1976. The book places each provision of the Convention in its historical context; provides commentary on the application of the Convention by the UK, the US, and other States; and thoroughly examines topical problems in the field including the abuse of diplomatic immunity and terrorist violence. This updated edition also highlights important new trends in the application of the Convention regime. It explores the interaction between State and diplomatic immunity (as shown in the Pinochet case), examines methods of establishing and conducting diplomatic relations under conditions of physical danger, and looks at increased evidence of disregard for the rules of secrecy in diplomatic communications. The book also explores the greater latitude for diplomats to 'interfere' in the internal affairs of the receiving State in the interest of protecting human rights and evaluates the impact of adoption of the UN Convention on Jurisdictional Immunities of States and their Property.